Magnesium Alloys Selected Issue - Tański, Tomasz; Borek, Wojciech; Król, Mariusz (IntechOpen, 2018)
Classical magnesium alloys are a combination of aluminium, magnesium, manganese and zinc. Magnesium combined with lithium forms ultralight alloys that have many uses. Since it is a reasonable material, it offers great possibilities and is constantly tested at various angles of applications and properties. Magnesium, previously used for military purposes, seems to fit perfectly to the requirements of the currently prevailing technology. Low density with appropriate mechanical properties (strength, high operating temperature), good foundry properties (high castability and low shrinkage), vibration damping ability and cost-effectiveness of recycling seem to be an ideal response to market needs. All things considered, magnesium alloys are the perfect material used in various industries starting from the automotive industry, through sport, electronics up to the space industry and defence. This book is written by experts in various areas of magnesium science and technology. It gives a general idea of modern advancements in theory and practical purposes of magnesium alloys. The book reports fundamental aspects of corrosion types and details about magnesium alloys designed to work in elevated temperatures and superplastic behaviour. Fundamentals, broad experience, theory as well as complex technological aspects make this work helpful for engineers and scientists from all over the world.